Analysis and characterization of residual salts from lithium carbonate industry: Their potential uses for thermal storage systems - Pablo R. Dellicompagni; Judith Franco; Julia Santapaola; Victoria Flexer; Silvana Flores Larsen (Next Energy)
The increasing demand for clean energy and the urgent need to reduce greenhouse gas emissions have led to a growing awareness of the importance of thermal energy storage systems in the diversification of the electric matrix. Sensible heat and latent heat storage are the two main techniques, and the choice of storage system depends on the melting point of the substances and the thermal energy required for the processes. This study focused on waste salts obtained from the production process of lithium carbonate. The thermophysical properties of these salts, including specific heat, density, and thermal stability, were examined through various characterization techniques such as X-ray diffraction, chemical analysis, scanning electron microscopy, thermogravimetry, and differential scanning calorimetry. The results revealed promising thermal properties, chemical stability, and physical availability of the waste salts. Additionally, the study explored the potential benefits of reutilizing these waste salts, such as reducing environmental impact, promoting circular economy principles, and creating new market opportunities for commercial products. Overall, this research provides valuable insights into the thermophysical properties of waste salts from lithium carbonate production. The main results are heat capacity in the solid phase (0.767–3.143 J/g°C) and storable thermal energy (114–1153 TWht). These findings contribute to the design and optimization of thermal energy storage systems, highlighting the potential for sustainable and efficient energy storage solutions in the context of global clean energy transitions.